2010
DOI: 10.1017/s0033291709992054
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive functioning in chronic fatigue syndrome: a meta-analysis

Abstract: Persons with CFS demonstrate moderate to large impairments in simple and complex information processing speed and in tasks requiring working memory over a sustained period of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
121
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(143 citation statements)
references
References 85 publications
17
121
1
4
Order By: Relevance
“…The levels of attention dysfunction found in this study appear to be consistent with deficits found in other studies (Busichio, et al, 2004;Capuron, et al, 2006;Cockshell & Mathias, 2010;DeLuca, et al, 1997). In addition, attention was the primary impairment in our sample.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The levels of attention dysfunction found in this study appear to be consistent with deficits found in other studies (Busichio, et al, 2004;Capuron, et al, 2006;Cockshell & Mathias, 2010;DeLuca, et al, 1997). In addition, attention was the primary impairment in our sample.…”
Section: Discussionsupporting
confidence: 92%
“…Participants showed poor performance in motor functioning, consistent with some studies (Busichio et al, 2004;Claypoole et al, 2007) but not others (Cockshell & Mathias, 2010). These inconsistencies may be the result of instrument heterogeneity in the assessment of this function.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…4 Patients who suffer from ME/CFS often report that they require increased mental effort, relative to that required before the onset of their illness, to complete everyday activities that require cognition. Experimentally, ME/CFS patients perform poorly, relative to controls, at tasks assessing attentional and working memory capacity [10][11][12][13]. Furthermore, a number of recent neuroimaging studies have shown increased brain activation in ME/CFS patients relative to control participants during cognitive tasks [14][15][16].…”
Section: Introductionmentioning
confidence: 99%